The Sixty-five Roses of Cystic Fibrosis: A Report of Two Autopsy Cases with Kidney Involvement - Stoyanov, George S (Cureus, 2019)
Cystic fibrosis (CF), also commonly referred to as mucoviscidosis, is a multigene related disorder, involving a defect in the CF transmembrane conductance regulator protein, with over 1,500 genes, being identified with the condition. The most commonly affected organs, often described in the literature, are the lungs, pancreas, intestines, and skin, which is one of the sites for early diagnostic testing. Herein we report two autopsy cases of CF, with multiorgan involvement and some rarely observed and reported changes. Two pediatric cases of clinically confirmed CF were referred for autopsy at the Department of General and Clinical Pathology, St. Marina University Hospital, Varna, Bulgaria. The first case was of a one-year-old female and the second of a six-month-old female. Both cases had classical CF-associated changes in the lungs, liver, pancreas, and small intestine. The kidneys although normal on gross inspection also had severe changes on histology with a compacted matter in the lumen of the distal tubules, some of which had undergone calcification. These histological renal changes are under-reported in literature, thus unlike the classical reported cystic changes we highlight lumen compaction and calcification as the primary histological hallmark in kidneys of patients with CF.